AN ANALYTICAL STUDY ON CONSUMER AWARENESS AND PERCEPTION OF HOSPITALS’ DIGITAL MARKETING EFFORTS - Narake, Swapnil; Dharmadhikari, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores consumer awareness and perceptions of digital marketing strategies employed by hospitals, focusing on social media presence, email newsletters, online advertisements, and their impact on understanding hospital services. As hospitals increasingly turn to digital platforms to reach patients, understanding consumer responses to these strategies is critical for effective engagement. The research utilizes a quantitative approach, with a sample of 65 respondents. Data were collected through a structured questionnaire, measuring awareness and perceptions of hospital digital marketing initiatives. The study tests three hypotheses related to consumer awareness of hospitals on social media, email communications, and online advertisements using one-sample t-tests. The results reveal a high level of consumer awareness regarding hospitals’ social media presence and online advertisements, with mean scores significantly above the neutral value of 3. However, awareness through email newsletters and digital communication channels showed no significant difference from the neutral point, indicating a lower engagement level. These findings align with previous research indicating the increasing role of digital marketing in healthcare but suggest that certain channels, like email marketing, may require more attention. The study contributes to the literature on healthcare marketing by highlighting the importance of targeted digital strategies to improve patient engagement and awareness. Managerial implications suggest hospitals should strengthen their digital presence, particularly in underutilized channels, and develop personalized marketing approaches. Limitations of the study include the small sample size and geographical focus, with recommendations for future research to examine broader populations and the impact of digital marketing on patient decision-making and hospital choice.